First direct evidence of spawning by Japanese sardine Sardinops melanosticta (Temminck and Schlegel) in the eastern Pacific Ocean - Miasara Andrew; Toby D. Auth; Kym C. Jacobson; Matthew T. Craig (Journal of Fish Biology, 2026)
In 2022 the presence of the Japanese sardine, Sardinops melanosticta (Temminck and Schlegel), was detected in the eastern Pacific Ocean, far outside its known western North Pacific range. The species was collected along with the Pacific sardine, Sardinops sagax (Jenyns), which is native to the eastern Pacific Ocean. Here, we report the first direct evidence for spawning by S. melanosticta in the eastern Pacific Ocean.

A tale of two heatwaves: variable daily growth and a broad diet enable neustonic larval cabezon to thrive during warm oceanic conditions - Megan N. Wilson; Richard D. Brodeur; Toby D. Auth; G. Curtis Roegner; Cheryl A. Morgan; Samantha M. Zeman; Su Sponaugle (Frontiers in Marine Science, 2025)
Effects of climate change on ocean ecosystem dynamics are widespread. Oceanographic conditions vital to biological communities have already shown changes, resulting in negative impacts on several of the world’s largest fisheries. The Northern California Current (NCC) is a highly productive system that supports many important fisheries. In addition to large-scale oceanographic forcing and seasonal up- and downwelling cycles, in the last decade, the NCC also experienced two distinct marine heatwaves (MHWs) that resulted in pervasive ecosystem alterations. The 2014–16 and 2019 MHWs had contrasting oceanic and atmospheric origins and different effects on ocean temperature, providing the opportunity to identify the mechanisms important to juvenile fish recruitment processes and how they may be differentially impacted by future warming scenarios. We utilized a five-year time series (2014, 2015, 2016, 2018, and 2019) of larval fish concentration, growth, and diet as a natural experiment to investigate the impact of MHWs as well as two neutral years on cabezon ( Scorpaenicthys marmoratus ). Findings include the first published measurement of larval cabezon daily growth rates. Mean growth rates were higher during MHWs, suggesting that elevated temperatures did not pose a major growth or survival challenge. Cabezon’s fast growth response to MHW conditions demonstrates that larval cabezon were able to sustain fast growth in warmer temperatures, and were not likely prey limited. Further, larval cabezon gut fullness did not differ significantly among years. Instead, differences in diet composition and prey quality varied with larval growth. Relative to slower-growing larvae, larval cabezon with high growth rates consumed larger prey items, including larval euphausiids and amphipods. Consistent with these patterns of larval growth, nearshore recruitment of juvenile cabezon was also high during MHW years. Our findings highlight the importance of phenological coupling, or matches in timing, between cabezon and euphausiid population dynamics in that larval cabezon exhibited fast growth when the timing of flexion was coupled with the euphausiid population transition to a larger, omnivorous larval stage. Results of this study suggest that larval cabezon’s variable growth and broad diet coupled with selection for large, nutrient dense prey may be a source of resilience for its population dynamics.

Marine Heatwaves and Climate‐Driven Warming Impact Availability of Sardine Subpopulations to Northeast Pacific Fishing Ports - Barbara A. Muhling; Juan P. Zwolinski; Peter T. Kuriyama; Toby D. Auth; Richard D. Brodeur; Sylvia P. A. Jiménez Rosenberg; Gerardo Aceves‐Medina; Jose Augusto Valencia Gasti; Michael G. Jacox; Mercedes Pozo Buil; Jerome Fiechter; Felipe J. Quezada Escalona; et al. (Fisheries Oceanography, 2025)
Changing ocean conditions are leading to spatial redistribution of many marine species, including those that support fisheries. A combination of gradual climate trends and shorter‐lived extreme events, such as marine heatwaves, can change the availability of species or stocks to fishing ports, impacting fishing communities and challenging fisheries management frameworks. Pacific sardine ( Sardinops sagax ) in the California Current System are currently considered as two subpopulations for management purposes. They are separated from each other using oceanographic conditions, based on the assumption that each subpopulation is associated with different habitats and geographic areas. However, as climate change and marine heatwaves lead to increasingly novel environmental conditions in the region, habitat‐based assignments may become impractical or unrealistic. In this study, we use generalized additive models to define sea surface temperature and surface chlorophyll conditions associated with the occurrence of multiple sardine life stages in fishery‐independent surveys conducted in the California Current System. We then show how the spatial distribution of habitats across life stages and putative subpopulations may be influenced by both gradual climate change and marine heatwaves. Our results highlight the potential impacts of changing ocean conditions near major sardine landing ports. During recent marine heatwaves, habitat associated with the northern subpopulation became less available to southern California Current ports, and this trend is projected to continue through the end of the 21st century. Future spatial shifts in sardine habitat may increasingly challenge the practicality of habitat‐based subpopulation separation and introduce more uncertainty into management frameworks.

Continuing Long‐Term Shifts in Larval Fish Phenology in the Southern California Current Ecosystem Are Matched by Rapid Advances in the North - Kathryn S. Chen; Colleen M. Petrik; Rebecca G. Asch; Andrew R. Thompson; Toby D. Auth (Global Change Biology, 2025)
Changing environmental conditions are leading to shifts in the timing of seasonal events globally. In the ocean, environmental cues affecting larval fish (ichthyoplankton) abundance may not be synchronized with factors optimizing larval and juvenile survival, making the study of ichthyoplankton phenology in the context of a changing environment critical. In the southern California Current Ecosystem (CCE), a major eastern boundary current upwelling system, significant long‐term shifts in larval fish phenology have been previously observed. To assess the stability of these estimates and extend them to the northern CCE, we evaluated multidecadal trends in ichthyoplankton abundance for 57 species from the California Cooperative Oceanic Fisheries Investigations (CalCOFI) and 25 species from the Newport Hydrographic Line (NH Line). We show that on average, larval fish phenology in the southern CCE has continued to advance with an estimated rate of −0.18 ± 0.05 day year −1 from 1951 to 2022, while phenology in the northern CCE has advanced at a rate of −0.48 ± 0.26 day year −1 from 1996 to 2023. Thirty‐nine percent of species showed significant advancing phenology, 12% exhibited delayed phenology, and 49% showed no long‐term linear change. A comparison analysis showed that species in these groups had similar rates of change between the two locations for the 1997–2017 period. Phenological shifts in the southern CCE tracked changes in the phenology of upper ocean temperature, zooplankton, and upwelling. These variables poorly explained shifts in the northern CCE, where short‐term effects of the El Niño–Southern Oscillation and the 2014–2016 marine heatwave on ichthyoplankton phenology were observed for some species. This research highlights regional variability and continuing phenological shifts in one of the world's most productive marine ecosystems.

State of the California Current Ecosystem report in 2022: a tale of two La Niñas - Andrew R. Thompson; Rasmus Swalethorp; Michaela Alksne; Jarrod A. Santora; Elliott L. Hazen; Andrew Leising; Erin Satterthwaite; William J. Sydeman; Clarissa R. Anderson; Toby D. Auth; Simone Baumann-Pickering; Timothy Baumgardner; et al. (Frontiers in Marine Science, 2024)
2022 marked the third consecutive La Niña and extended the longest consecutive stretch of negative Oceanic Niño Index since 1998-2001. While physical and biological conditions in winter and spring largely adhered to prior La Niña conditions, summer and fall were very different. Similar to past La Niña events, in winter and spring coastal upwelling was either average or above average, temperature average or below average, salinity generally above average. In summer and fall, however, upwelling and temperature were generally average or slightly below average, salinity was close to average and chlorophyll a was close to average. Again, as during prior La Niña events, biomass of northern/southern copepods was above/below average off Oregon in winter, and body size of North Pacific krill in northern California was above average in winter. By contrast, later in the year the abundance of northern krill dropped off Oregon while southern copepods increased and body sizes of North Pacific krill fell in northern California. Off Oregon and Washington abundances of market squid and Pacific pompano (indicators of warm, non-typical La Niña conditions) were high. In the 20 th century, Northern anchovy recruitment tended to be high during cold conditions, but despite mostly warm conditions from 2015-2021 anchovy populations boomed and remained high in 2022. Resident seabird reproductive success, which tended in the past to increase during productive La Niña conditions was highly variable throughout the system as common murre and pelagic cormorant, experienced complete reproductive failure at Yaquina Head, Oregon while Brandt’s cormorant reproduction was average. At three sampling locations off central California, however, common murre reproduction was close to or above average while both pelagic and Brandt’s cormorant were above average. California sealion reproduction has been above average each year since 2016, and pup weight was also above average in 2022, likely in response not to La Niña or El Niño but continuous high abundance of anchovy. The highly variable and often unpredictable physical and biological conditions in 2022 highlight a growing recognition of disconnects between basin-scale indices and local conditions in the CCE. “July-December 2022 is the biggest outlier from individual “strong” La Niña (events) ever going back to the 50s.” – Nate Mantua

State of the California Current Ecosystem in 2021: Winter is coming? - Andrew R. Thompson; Eric P. Bjorkstedt; Steven J. Bograd; Jennifer L. Fisher; Elliott L. Hazen; Andrew Leising; Jarrod A. Santora; Erin V. Satterthwaite; William J. Sydeman; Michaela Alksne; Toby D. Auth; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2022)
In late 2020, models predicted that a strong La Niña would take place for the first time since 2013, and we assessed whether physical and biological indicators in 2021 were similar to past La Niñas in the California Current Ecosystem (CCE). The Pacific Decadal Oscillation and Oceanic Niño Index indeed remained negative throughout 2021; the North Pacific Gyre Oscillation Index, however, remained strongly negative. The seventh largest marine heatwave on record was unexpectedly present from April to the end of 2021; however, similar to past La Niñas, this mass of warm water mostly remained seaward of the continental shelf. As expected from past La Niñas, upwelling and chlorophyll were mostly high and sea surface temperature was low throughout the CCE; however, values were close to average south of Point Conception. Similar to past La Niñas, abundances of lipid-rich, northern copepods off Oregon increased. In northern California, unlike past La Niñas, the body size of North Pacific krill ( Euphausia pacifica ) was close to average. Predictably, overall krill abundance was above average in far northern California but, unexpectedly, below average south of Cape Mendocino. Off Oregon, similar to past La Niñas, larval abundances of three of six coastal species rose, while five of six southern/offshore taxa decreased in 2021. Off California, as expected based on 2020, Northern Anchovy ( Engraulis mordax ) were very abundant, while Pacific Sardine ( Sardinops sagax ) were low. Similar to past La Niñas, market squid ( Doryteuthis opalescens ) and young of the year (YOY) Pacific Hake ( Merluccius pacificus ), YOY sanddabs ( Citharichthys spp.), and YOY rockfishes ( Sebastes spp.) increased. Southern mesopelagic (e.g., Panama lightfish Vinciguerria lucetia , Mexican lampfish Triphoturus mexicanus ) larvae decreased as expected but were still well above average, while northern mesopelagic (e.g., northern lampfish Stenobrachius leucopsarus ) larvae increased but were still below average. In line with predictions, most monitored bird species had above-average reproduction in Oregon and California. California sea lion ( Zalophus californianus ) pup count, growth, and weight were high given the abundant Anchovy forage. The CCE entered an enduring La Niña in 2021, and assessing the responses of various ecosystem components helped articulate aspects of the system that are well understood and those that need further study.

Corrigendum: State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2022)

State of the California Current 2019–2020: Back to the Future With Marine Heatwaves? - Edward D. Weber; Toby D. Auth; Simone Baumann-Pickering; Timothy R. Baumgartner; Eric P. Bjorkstedt; Steven J. Bograd; Brian J. Burke; José L. Cadena-Ramírez; Elizabeth A. Daly; Martin de la Cruz; Heidi Dewar; John C. Field; et al. (Frontiers in Marine Science, 2021)
The California Current System (CCS) has experienced large fluctuations in environmental conditions in recent years that have dramatically affected the biological community. Here we synthesize remotely sensed, hydrographic, and biological survey data from throughout the CCS in 2019–2020 to evaluate how recent changes in environmental conditions have affected community dynamics at multiple trophic levels. A marine heatwave formed in the north Pacific in 2019 and reached the second greatest area ever recorded by the end of summer 2020. However, high atmospheric pressure in early 2020 drove relatively strong Ekman-driven coastal upwelling in the northern portion of the CCS and warm temperature anomalies remained far offshore. Upwelling and cooler temperatures in the northern CCS created relatively productive conditions in which the biomass of lipid-rich copepod species increased, adult krill size increased, and several seabird species experienced positive reproductive success. Despite these conditions, the composition of the fish community in the northern CCS remained a mixture of both warm- and cool-water-associated species. In the southern CCS, ocean temperatures remained above average for the seventh consecutive year. Abundances of juvenile fish species associated with productive conditions were relatively low, and the ichthyoplankton community was dominated by a mixture of oceanic warm-water and cosmopolitan species. Seabird species associated with warm water also occurred at greater densities than cool-water species in the southern CCS. The population of northern anchovy, which has been resurgent since 2017, continued to provide an important forage base for piscivorous fishes, offshore colonies of seabirds, and marine mammals throughout the CCS. Coastal upwelling in the north, and a longer-term trend in warming in the south, appeared to be controlling the community to a much greater extent than the marine heatwave itself.

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

Predictability of Species Distributions Deteriorates Under Novel Environmental Conditions in the California Current System - Barbara A. Muhling; Stephanie Brodie; James A. Smith; Desiree Tommasi; Carlos F. Gaitan; Elliott L. Hazen; Michael G. Jacox; Toby D. Auth; Richard D. Brodeur (Frontiers in Marine Science, 2020)

Major Shifts in Pelagic Micronekton and Macrozooplankton Community Structure in an Upwelling Ecosystem Related to an Unprecedented Marine Heatwave - Richard D. Brodeur; Toby D. Auth; Anthony Jason Phillips (Frontiers in Marine Science, 2019)

Phenological and distributional shifts in ichthyoplankton associated with recent warming in the northeast Pacific Ocean - Toby D. Auth; Elizabeth A. Daly; Richard D. Brodeur; Jennifer L. Fisher (Global Change Biology, 2018)
Understanding changes in the migratory and reproductive phenology of fish stocks in relation to climate change is critical for accurate ecosystem‐based fisheries management. Relocation and changes in timing of reproduction can have dramatic effects upon the success of fish populations and throughout the food web. During anomalously warm conditions (1–4°C above normal) in the northeast Pacific Ocean during 2015–2016, we documented shifts in timing and spawning location of several pelagic fish stocks based on larval fish samples. Total larval concentrations in the northern California Current ( NCC ) during winter (January–March) 2015 and 2016 were the highest observed since annual collections first occurred in 1998, primarily due to increased abundances of Engraulis mordax (northern anchovy) and Sardinops sagax (Pacific sardine) larvae, which are normally summer spawning species in this region. Sardinops sagax and Merluccius productus (Pacific hake) exhibited an unprecedented early and northward spawning expansion during 2015–16. In addition, spawning duration was greatly increased for E. mordax, as the presence of larvae was observed throughout the majority of 2015–16, indicating prolonged and nearly continuous spawning of adults throughout the warm period. Larvae from all three of these species have never before been collected in the NCC as early in the year. In addition, other southern species were collected in the NCC during this period. This suggests that the spawning phenology and distribution of several ecologically and commercially important fish species dramatically and rapidly changed in response to the warming conditions occurring in 2014–2016, and could be an indication of future conditions under projected climate change. Changes in spawning timing and poleward migration of fish populations due to warmer ocean conditions or global climate change will negatively impact areas that were historically dependent on these fish, and change the food web structure of the areas that the fish move into with unforeseen consequences.

Distribution and community structure of ichthyoplankton from the northern and central California Current in May 2004–06 - TOBY D. AUTH (Fisheries Oceanography, 2008)
The distributions, concentrations, and community structure of pelagic larval fishes collected from the central and northern California Current in the northeast Pacific Ocean during May 2004, 2005, and 2006 were analyzed to investigate inter‐annual, latitudinal, cross‐shelf, and depth‐stratified variability. The inter‐annual climate‐induced variability during the sampling period provided a unique opportunity to observe how larval fish communities adjust to rapidly changing environmental conditions. The 170 depth‐stratified samples collected from three cruises yielded 14 819 fish larvae from 56 taxa representing 23 families. Dominant larval taxa were Engraulis mordax , Citharichthys spp., Sebastes spp., and Stenobrachius leucopsarus . Larval concentrations decreased significantly in 2006 from 2004 and 2005 levels following the anomalous oceanic conditions observed in 2005 and decreased water temperature in 2006. Larvae were generally found in higher concentrations at northern (>43°N) versus southern ( E. mordax and Citharichthys spp. found almost exclusively in the north during all sampled years. Inter‐annual variability related to dynamic upwelling intensity was observed in cross‐shelf larval distributions, although concentrations of S. leucopsarus larvae consistently increased in the offshore direction, while larval Sebastes spp. were generally found in highest concentrations at intermediate stations along the shelf. Multivariate analyses revealed that latitude, station depth, and sea‐surface temperature were the most important factors explaining variability in larval concentrations. The present study shows that the ichthyoplankton community of the central and northern California Current changed dramatically in response to the variable environmental conditions of 2004–06.